2013
DOI: 10.1371/journal.pone.0059410
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease of Mineralcorticoid Receptor Drives Angiogenic Pathways in Colorectal Cancer

Abstract: Angiogenesis plays a crucial role in tumor growth and progression. Low expression of mineralocorticoid receptor (MR) in several malignant tumors correlates with disease recurrence and overall survival. Previous studies have shown that MR expression is decreased in colorectal cancer (CRC). Here we hypothesize that decreased MR expression can contribute to angiogenesis and poor patient survival in colorectal malignancies. In a cohort of CRC patients, we analyzed tumor MR expression, its correlation with tumor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…The functional role of NR3C2 in tumorigenesis is not clear. An association between lower NR3C2 expression and increased angiogenesis has been described in colon cancer (19). EMT is a critical event in the progression of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The functional role of NR3C2 in tumorigenesis is not clear. An association between lower NR3C2 expression and increased angiogenesis has been described in colon cancer (19). EMT is a critical event in the progression of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, a decrease in NR3C2 expression is associated with poor prognosis in lung and colorectal cancer (18, 19). However, the role of NR3C2 has not been described in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nie et al () found that activation of NR3C2 could inhibit the Warburg effect in hepatocellular carcinoma by modulating miR‐338‐3p/pyruvate kinase. In colorectal cancer, some studies have demonstrated that decreased MR expression is associated with increased microvascular density and poor patient survival through the direct inhibition of dysregulated VEGFA expression (Di Fabio et al, ; Tiberio et al, ). Similar results have also been demonstrated in early stage cervical carcinoma (Huang et al, ), pancreatic cancer (Yang et al, ), breast cancer (Nan, Dorgan, & Rebbeck, ), and lung cancer (Jeong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, an observed decrease in the expression of MR in cancerous tissue in comparison to the adjacent normal mucosa has attributed MR a tumor suppressive role [6]. Tiberio et al [7] further investigated how MR expression correlated with patient survival in colorectal carcinomas. In this study, the expressions of MR and tumor microvessel density marker protein CD34 were evaluated in tumor and normal colorectal mucosa by IHC, and an inverse correlation of expression was detected between them in colorectal cancers.…”
Section: Colorectal Cancermentioning
confidence: 99%